CXCL13-neutralizing Antibody Alleviate Chronic Skeletal Muscle Degeneration in a Mouse Model - Xie, Zhongcheng; Yang, Jimin; Jiao, Chunmeng; Chen, Hui; Ouyang, Siyu; Liu, Zhiyang; Hou, Qin; Liu, Jifeng (Current Molecular Medicine, 2025)
Introduction Skeletal muscle degeneration is a common effect of chronic muscle injuries, including fibrosis and fatty infiltration, which is the replacement of pre-existing parenchymal tissue by extracellular matrix proteins and abnormal invasive growth of fibroblasts and adipocytes. Methods This remodeling limits muscle function and strength, eventually leading to reduced quality of life for those affected. Chemokines play a major role in the regulation of immunocyte migration, inflammation, and tissue remodeling and are implicated in various fibrotic and degenerative diseases. In this study, we aimed to investigate the role of the B-cell chemokine CXCL13 in the gastrocnemius muscle of the Achilles tendon rupture model mouse. We hypothesize that CXCL13 may promote fibrosis and aggravate skeletal muscle degeneration. We performed RNA sequencing and bioinformatics analysis of gastrocnemius muscle from normal and model mice to identify differentially expressed genes and signal pathways related to skeletal muscle degeneration and fibrosis. Results Our results show that CXCL13 is highly expressed in chronically degenerating skeletal muscle. Furthermore, CXCL13-neutralising antibodies with therapeutic potential were observed to inhibit fibrosis and adipogenesis in vivo and in vitro. Conclusion Our study reveals the underlying therapeutic implications of CXCL13 inhibition for clinical intervention in skeletal muscle degeneration, thereby improving patient prognosis.
Keywords: CXCL13